How Microglia Manages Non-cell Autonomous Vicious Cycling of Aβ Toxicity in the Pathogenesis of AD - YunHee Seol; Soomin Ki; Hannah L. Ryu; Sooyoung Chung; Junghee Lee; Junghee Lee; Hoon Ryu; Hoon Ryu (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease and a common form of dementia that affects cognition and memory mostly in aged people. AD pathology is characterized by the accumulation of β-amyloid (Aβ) senile plaques and the neurofibrillary tangles of phosphorylated tau, resulting in cell damage and neurodegeneration. The extracellular deposition of Aβ is regarded as an important pathological marker and a principal-agent of neurodegeneration. However, the exact mechanism of Aβ-mediated pathogenesis is not fully understood yet. Recently, a growing body of evidence provides novel insights on the major role of microglia and its non-cell-autonomous cycling of Aβ toxicity. Hence, this article provides a comprehensive overview of microglia as a significant player in uncovering the underlying disease mechanisms of AD.